An Inhibitor of Grp94 Inhibits OxLDL-Induced Autophagy and Apoptosis in VECs and Stabilized Atherosclerotic Plaques - Wei, Qun; Ren, Hui; Zhang, Jun; Yao, Wen; Zhao, Baoxiang; Miao, Junying (Frontiers in Cardiovascular Medicine, 2021)
Background: Oxidized low-density lipoprotein (oxLDL) induces vascular endothelial cell (VEC) injury and atherosclerosis through activating endoplasmic reticulum stress. Expression of glucose-regulated protein 94 (Grp94) is induced by endoplasmic reticulum stress and Grp94 is involved in cardiovascular diseases. The aim of this study was to study the role of Grp94 in oxLDL-induced vascular endothelial cell injury and atherosclerosis. Methods and Results: An inhibitor of Grp94, HCP1, was used to investigate the role of Grp94 in oxLDL-induced VEC injury in human umbilical vein endothelial cells and atherosclerosis in apolipoprotein E-/- mice. Results showed that HCP1 inhibited autophagy and apoptosis induced by oxLDL in VECs. And we found that Grp94 interacted with adenosine monophosphate-activated protein kinase (AMPK) and activated its activity. HCP1 inhibited AMPK activity and overexpression of Grp94 blocked the effect of HCP1. Besides, HCP1 activated the activity of mechanistic target of rapamycin complex 1 (mTORC1), co-treatment with AMPK activator acadesine eliminated the effect of HCP1 on mTORC1 activity as well as autophagy. In apolipoprotein E-/- mice, HCP1 suppressed autophagy and apoptosis of atherosclerotic plaque endothelium. In addition, HCP1 increased the content of collagen, smooth muscle cells and anti-inflammatory macrophages while reduced the activity of MMP-2/9 and pro-inflammatory macrophages in atherosclerotic lesion. Conclusion: HCP1 inhibited oxLDL-induced VEC injury and promoted the stabilization of atherosclerotic plaque in apoE-/- mice. Grp94 might be a potential therapeutic target in clinical treatment of atherosclerosis.